Thank You to Our 2019 Reviewers. Issue 8 (4th August 2020) - Raymond, Peter; Matsumoto, Katsumi; Mikaloff‐Fletcher, Sara; Houlton, Benjamin
Abstract: Members of the editorial board of Global Biochemical Cycles express their appreciation to those who served as peer reviewers for the journal in its inaugural year. Key Points: Peer review is a critical component of the scientific process; having scientists from the same field not directly involved in the work constantly reviewing work for accuracy, significance, and originality leads to the high standards that define all AGU journals The hard work that goes into peer review for AGU journals has solidified it as a trusted outlet for communicating scientific findings; as an editor I can also say that the process generally improves the quality and impact of submittals In 2019 GBC received 437 reviews from 338 of our peers; thanks, to you all for your commitment to advancing science and the AGU